2008
DOI: 10.1063/1.2946446
|View full text |Cite
|
Sign up to set email alerts
|

Structure, paramagnetic defects and light-emission of carbon-rich a-SiC:H films

Abstract: The effect of vacuum annealing on local structure reconstruction, evolution of photoluminescence ͑PL͒ and paramagnetic defects in carbon-rich a-Si 1−x C x : H films ͑x = 0.7͒ was studied. Strong enhancement of visible ͑white-green͒ PL was observed after annealing in the temperature range of 400-500°C. Such enhancement was correlated with increasing of the concentration of carbon-hydrogen bonds in Si: C u H n accompanied with increase in the fluctuation of the interatomic potential. Complete disappearance of PL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…4) ) and in the asdeposited a-Si 0.3 H 0.7 :H sample (N s is about 4·10 19 cm -3 ), one can see that the PL intensity differs by 10 times, while the concentration of paramagnetic centers remains almost the same. It is obvious from these observations that the concentration of paramagnetic defects is not the only parameter determining the PL efficiency in a-Si 1−x C x :H. In the previous report [12], it was suggested that the PL efficiency in a-Si 1−x C x :H films can be increased by enhancement of spatial localization of photo-excited electron-hole pairs caused by increasing the concentration of C-H bonds and corresponding increase of spatial fluctuations of the interatomic potential. In frame of this hypothesis, one can reasonably suggest that introducing Si-O bonds would also increase fluctuations of this potential and enhances localization of photo-excited electron-hole pairs in the SiC network.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…4) ) and in the asdeposited a-Si 0.3 H 0.7 :H sample (N s is about 4·10 19 cm -3 ), one can see that the PL intensity differs by 10 times, while the concentration of paramagnetic centers remains almost the same. It is obvious from these observations that the concentration of paramagnetic defects is not the only parameter determining the PL efficiency in a-Si 1−x C x :H. In the previous report [12], it was suggested that the PL efficiency in a-Si 1−x C x :H films can be increased by enhancement of spatial localization of photo-excited electron-hole pairs caused by increasing the concentration of C-H bonds and corresponding increase of spatial fluctuations of the interatomic potential. In frame of this hypothesis, one can reasonably suggest that introducing Si-O bonds would also increase fluctuations of this potential and enhances localization of photo-excited electron-hole pairs in the SiC network.…”
Section: Resultsmentioning
confidence: 99%
“…Residual oxygen contamination in our films was estimated using Auger electron spectroscopy to be up to 7…10 at.%, so that the contribution of Si-O vibrations should be taken into account. Unfortunately, it is not possible to separate correctly hydrogen-and oxygenrelated absorption bands, but, basing on our previous experience [12], we assume that hydrogen-related contribution dominates in as-deposited samples. From Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Improvement of the electronic properties of these materials to device quality has been due to appropriate incorporation of hydrogen ("hydrogenation") that passivates a large fraction of the paramagnetic defects. In our previous studies [6,7] we established a clear correlation between vacuum annealing temperature and photoluminescence (PL) / paramagnetic defect concentration of stoichiometric and carbon-rich a-Si 1 − x C x :H films. It was shown that increasing the anneal temperature up to 450°C decreases the paramagnetic defects concentration and maximizes PL.…”
Section: Introductionmentioning
confidence: 94%
“…It was shown that increasing the anneal temperature up to 450°C decreases the paramagnetic defects concentration and maximizes PL. Further increase of annealing temperature up to 650°C resulted in quenching of PL, increase of paramagnetic defects concentration and precipitation of carbon nanoclusters [6][7][8]. The detailed electrical properties of these films have not been studied.…”
Section: Introductionmentioning
confidence: 94%